Physico‐Chemical Properties of Magnetic Dicationic Ionic Liquids with Tetrahaloferrate Anions. Issue 1 (4th January 2023) - Zafar, Anham; Imtiaz‐ud‐Din,; Palgrave, Robert G.; Muhammad, Haji; Yousuf, Sammer; Evans, Tim
Abstract: A series of imidazolium‐based symmetrical and asymmetrical dicationic ionic liquids (DcILs) with alkyl spacers of different length and with [FeCl3 Br] − as counter ion have been synthesized. The synthesized DcILs are characterized by using FTIR and Raman spectroscopy as well as mass spectrometry, along with single‐crystal XRD analysis. Physicochemical properties such as solubility, thermal stability and magnetic susceptibility are also measured. These compounds show low melting points, good solubility in water and organic solvents, thermal stability, and paramagnetism. The products of molar susceptibility and temperature (χmol ⋅T) for the synthesized DcILs have been found between 4.05 to 4.79 emu mol −1  K Oe −1 and effective magnetic moment values have also been determined to be compared to that expected from the spin‐only approximation. Abstract : A series of dicationic ionic liquids based on symmetrically and asymmetrically substituted imidazolium units combined with magnetic tetrahaloferrate anions have been synthesized and their magnetic and physical properties have been measured.